King of greed - Huang, Ana (Huang, Ana. Kings of sin, 2023)
"Powerful, brilliant, and ambitious, Dominic Davenport clawed his way up from nothing to become the King of Wall Street. He has everything-a beautiful home, a beautiful wife, and more money than he could spend in a lifetime. But no matter how much he accumulates, he's never satisfied. In his endless quest for more, he drives away the only person who saw him as enough. It isn't until she's gone that he realizes there may be more to life than riches and glory...but by then, it may be too late. Kind, intelligent, and thoughtful, Alessandra Davenport has played the role of trophy wife for years. She stood by her husband while he built an empire, but now that they've reached the top, she realizes he's no longer the man she fell for. When it becomes clear that she'll always come second to his work, she finally takes charge of her life and puts herself first-even if it means leaving the only man she's ever loved. But what she didn't count on was his refusal to let her go...or for him to fight for their marriage, no matter what it takes"--